Safety and Productivity in Underground Coal Mining - Sider, Hal (The Review of Economics and Statistics, 1983)
An extended Cobb-Douglas production function is developed and estimated in order to examine the extent to which the decline in measured productivity in underground coal mining can be attributed to (1) changes in safety conditions which reflect movement along a product transformation frontier relating safety and marketable output and (2) a shift downward of the entire transformation surface. The model incorporates work-related accidents as a joint output and accounts for the discrete nature of the technological choices available in underground mining. The results indicate that movements along the product transformation curve relating accidents and marketable output do not account for the decline in measured productivity. This decline instead reflects a shift downward of this frontier - a real decline in potential production of marketable output. The non-linear pattern in technological change parameters and differences in these parameters across technologies indicate that a variety of factors have influenced productivity trends including CMHSA and the 1974 contract between union and management. 14 references